Antologias dos homens infames : um ensaio sobre a palavra do interior do cárcere - Carvalho, Juliano Gomes de (2014)
The presented paper addresses the issues related to the effects of the prison testimony in de(re)structuring of legal discourse that ignores their expressions. It is intended to expose the original stories, to feel, out of an instrumental rationality, the main criminological issue, the suffering. Thus, we seek in this inviting essays path, the discomfort of a answer in suspension, but modifier in their silences and pauses in a linguistic alterity. This way, as a firm commitment of ethical approach, using philosophical questions about alterity mainly influenced by Prof. Ricardo Timm de Souza, we propose the encounter with the other, and due trauma that places responsibility on criminology when it opens the different.